Specialized adaptations allow vent-endemic crabs (Xenograpsus testudinatus) to thrive under extreme environmental hypercapnia - Allen, Garett J. P. (Sci Rep, 2020)
Shallow hydrothermal vent environments are typically very warm and acidic due to the mixing of ambient seawater with volcanic gasses (> 92% CO(2)) released through the seafloor making them potential ‘natural laboratories’ to study long-term adaptations to extreme hypercapnic conditions. Xenograpsus testudinatus, the shallow hydrothermal vent crab, is the sole metazoan inhabitant endemic to vents surrounding Kueishantao Island, Taiwan, where it inhabits waters that are generally pH 6.50 with maximum acidities reported as pH 5.50. This study assessed the acid–base regulatory capacity and the compensatory response of X. testudinatus to investigate its remarkable physiological adaptations. Hemolymph parameters (pH, [HCO(3)(−)], [Formula: see text] , [NH(4)(+)], and major ion compositions) and the whole animal’s rates of oxygen consumption and ammonia excretion were measured throughout a 14-day acclimation to pH 6.5 and 5.5. Data revealed that vent crabs are exceptionally strong acid–base regulators capable of maintaining homeostatic pH against extreme hypercapnia (pH 5.50, 24.6 kPa [Formula: see text] ) via HCO(3)(−)/Cl(−) exchange, retention and utilization of extracellular ammonia. Intact crabs as well as their isolated perfused gills maintained [Formula: see text] tensions below environmental levels suggesting the gills can excrete CO(2) against a hemolymph-directed [Formula: see text] gradient. These specialized physiological mechanisms may be amongst the adaptations required by vent-endemic animals surviving in extreme conditions.